Aplikasi Pemetaan Pertambangan Berbasis Web GIS (Geographic Information System) di Sulawesi Utara - Christofel Owen Tendean; Ferdinan Ivan Sangkop; Vivi Peggie Rantung (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2023)
This research aims to apply GIS (geographic information system) to a website-based mining mapping application in North Sulawesi Province as a source of information that can be accessed to facilitate the monitoring of mining activities. The public can find out the location of mining areas and mining information. The method used to identify stages in the system is the waterfall method. The system was created using Sublime Text 3, PHP as a programming language, and a MySQL database. The research results show that the implementation and testing of the application are smooth, with every feature functioning optimally. Users get information from the website regarding mining coordinates (locations) and their distribution, as well as information from each mining location.